'Doctrina Deo vivendi': William Ames, the Nature and Sources of His Voluntarism. Issue 1 (2nd January 2020) - Yagi, Takayuki
ABSTRACT: To establish his vision of theology as the doctrine of 'living to God, ' William Ames, the English puritan theologian exiled in The Netherlands, strongly emphasized the will as the seat of faith. This prominence has often been interpreted as an extreme version of voluntarism eliminating the intellective elements altogether and regarded as something outside mainstream, Reformed orthodoxy. However, when analysed through the distinction between habit and action, it will be clear that Ames's emphatic statements on the will reflect his concern for the singularity of virtue, and that he did assign some roles to the intellect in terms of the action of faith. Therefore, the difference over the question of the seat of faith is highly technical in nature and should not be exaggerated. Ames argued for the priority of the will over the intellect by drawing from Scotist sources, which was compatible with the Thomistic idea of premotion.